Efectos fisicoquímicos y sensoriales del arroz malteado y pulpa de maracuyá como sustitutos parciales de cebada en cerveza artesanal tipo IPA - Barreto Zambrano, Juan Francisco (2021)
The objective of the research was to determine the physicochemical and sensory effects of malted rice and passion fruit pulp as adjuncts in an IPA-type craft beer. The factors under study were: percentage of malted rice (10 and 30) and percentage of passion fruit pulp (1, 3 and 5). A bifactorial arrangement A x B was applied in Completely Random Design (DCA), with 6 treatments, 3 repetitions were carried out, resulting in 18 experimental units. The experimental unit was 3000 ml of craft beer with the aforementioned adjuncts. The physicochemical, microbiological and sensory characteristics were evaluated. In the physicochemical, the variables of pH, acidity and degrees of alcohol showed significant differences between treatments with an average value of pH of 2.91; acidity of 1.61%; density of 1,026 g / ml and a percentage of alcohol degrees of 3.23%. In the microbiological analyzes, values from 1.4x103 to 6.0x103 CFU / ml were obtained. In the sensory analysis carried out by means of a preference test, T3 was the best treatment (10% malted rice and 5% passion fruit pulp). The values found reveal that the use of malted rice and passion fruit pulp as brewing adjuncts influences the physicochemical and sensory characteristics of IPA-type craft beer.